KATEGORI KONSERVASI VEGETASI TUMBUHAN BAWAH DI LAHAN BERA WOMNOWI DISTRIK SIDEY MANOKWARI PAPUA BARAT - Slamet Arif Susanto; Heru Joko Budirianto; Agatha Cecilia Maturbongs (VOGELKOP: Jurnal Biologi, 2019)
Trees vegetation are obviously dominate at the old fallow lands of Papua Indonesian. Fallow lands in the edge of primary forest is generally at Sidey District Manokwari. The purpose of this study is to determinate understory cover vegetation conservation based list of IUCN at the fallow land Womnowi Sidey Manokwari. An inventory of vegetation has done using analysis of vegetation―continuous line sampling technique, 2 x 2 meters for sampling seedlings and understory non-woody plant cover and 5 x 5 for saplings. At one hectare fallow land we found 1482 an individual of 122 species understory cover, only 158 an individual of 22 species had entered in IUCN redlist. Species with status least concern (LC) are dominate (>80%) compare with status data deficient (DD), near threatened (NT), and vulnerable (V). The important value index (IVI) of species on list IUCN showing 22.60% at seedlings and non-woody understory cover and 19.81% at the saplings phase. Aglaia odorata Lour.(seedling and sapling) is LC category, Intsia bijuga (Colebr.) Kuntze (seedling) V category, and Pandanus tectorius var., uapensis (non-woody plant) DD category, each species is the only one. The further study should be more intensive compare primary forest and old fallow lands of Papua―the conservation list of understory cover vegetation is lowest, so we conclude this is obviously understory vegetation at old fallow lands.Key word: fallow land, conservation, Sidey, understory, analysis of vegetation